Improvements in machinability of zinc oxide ceramics by laser-assisted milling - Muženič, David (Strojniški vestnik, 2019)
In this paper, an attempt is made to advance the understanding of Laser-Assisted Milling (LAMill) of zinc oxide (ZnO) electronic ceramics. A series of conventional milling and LAMill experiments with varying laser power were conducted to determine the effect of laser assistance on the machinability of this material. Improved machinability in terms of reduction in machined surface roughness and edge chipping was achieved by adjusting laser power. At an optimal laser power of 120 W, determined for the machining parameters used, Ra and Rz were reduced by 37 % and 46 %, respectively, while the average and maximum chipping widths were reduced by 15 % and 17 %, respectively.
Keywords: edge chipping; frezanje z lasersko asistenco; hrapavost obdelane površine; keramika na bazi cinkovega oksida; krušenje robov; laser-assisted milling; machinability; obdelovalnost; surface roughness; zinc oxide (ZnO) ceramics